A biographical study of namesake John F. Tinker on the landmark legal case Tinker et al. v. The Des Moines Independent Community School District et al. - Wolfe-Dawson, Leigh, author; Harbour, Clifford P., advisor (Colorado State University. Libraries, 2008)
The purpose of this biographical study was to understand the effect of the case Tinker et al. v. The Des Moines Independent Community School District et al. circa 1965-1969, on namesake John F. Tinker, circa 2008. John Tinker was involved in a landmark 1969 United States Supreme Court decision nearly 40 years ago. He was 15 years old when he wore a black armband to school to protest the Vietnam War; he is 57 now. In legal and educational environments, Tinker is known as a name on a school-related legal decision, but there is a person behind that name. While there is abundant information about his legal case, not much is known about the namesake. This study attempted to understand how Tinker experienced his legal case and how he understands its effect on his life. This study centered on John Tinker's own voice. Through in-depth, open-ended, one-on-one, face-to-face, voice-to-voice, and computer-to-computer conversations, an account of his life using his own words emerged. What was discovered was that Tinker is a multi-faceted person and the Tinker legal case is only one aspect of his full and unique life. This study is important because Tinker is a living being who as a teenager was involved in an activity that culminated in a landmark decision by the United States Supreme Court. That legal decision holds today-40 years later-and affects every public school student in the United States.
Keywords: black armbands; Des Moines; education; First Amendment; iowa; symbolic speech; Tinker et al. v. The Des Moines Independent Community School District et al.; Tinker, John F.; biographies; law; school administration; educational administration